2022
DOI: 10.1590/0034-7167-2021-0498
|View full text |Cite
|
Sign up to set email alerts
|

Professional burnout of nursing team working to fight the new coronavirus pandemic

Abstract: Objective: to identify burnout and associated factors among nursing workers working in coping with COVID-19. Methods: a cross-sectional study, developed in four hospitals in a capital in southern Brazil. Sample (n=499) composed of nurses and nursing technicians/assistants, who answered an online form containing socio-occupational characterization and the Maslach Burnout Inventory. Descriptive and inferential statistical analysis was performed, including multiple comparison tests. Results: burnout was identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
10

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 23 publications
1
9
0
10
Order By: Relevance
“…Nurses with high levels of burnout had a higher degree of job dissatisfaction and were about to quit their jobs. On the other hand, a study by Magalhães et al [13] showed that only 12% of nurses experienced burnout. On the other hand, Dechasa et al [14] observed that out of 412 nurses participating in the study 183 (44.4%) nurses experienced burnout.…”
Section: Discussionmentioning
confidence: 94%
“…Nurses with high levels of burnout had a higher degree of job dissatisfaction and were about to quit their jobs. On the other hand, a study by Magalhães et al [13] showed that only 12% of nurses experienced burnout. On the other hand, Dechasa et al [14] observed that out of 412 nurses participating in the study 183 (44.4%) nurses experienced burnout.…”
Section: Discussionmentioning
confidence: 94%
“…In the analysis of the abstracts, 202 studies were excluded, leaving 57 studies in the sample. In addition, another six articles retrieved from the references of the studies included were added for analysis, totaling a sample of 62 articles (Appel et al., 2021; Arnetz et al., 2020; Bitencourt et al., 2021; Blanchard et al., 2022; Brown et al., 2023; Burstyn & Holt, 2022; Chapa‐Koloffon et al., 2021; Cohen et al., 2022; Côté et al., 2022; Crowe et al., 2022; Cruz et al., 2021; Cuccia et al., 2022; Dal'Bosco et al., 2020; De las Salas et al., 2021; Drager et al., 2022; El Gindi et al., 2022; Estes et al., 2021; Feingold et al., 2021; Freitas et al., 2021; Freitas et al., 2022; Guillen‐Burgos, Gomez‐Ureche, Acosta, et al., 2022; Guillen‐Burgos, Gomez‐Ureche, Renowitzky, et al., 2022; Gutierrez et al., 2022; Guttormson et al., 2022; Havaei, Ma, et al., 2021; Havaei, Smith, et al., 2021; Hendrickson et al., 2022; Hernandez et al., 2021; Hickling & Barnett, 2022; Ingle, 2021; Kim et al., 2021; Kovner et al., 2021; Machado et al., 2022; Magalhães et al., 2021; Martínez et al., 2020; Martínez‐Ponce et al., 2023; Melnyk et al., 2022; Mensinger et al., 2022; Merkle et al., 2022; Montoya et al., 2021; Obando et al., 2020; Oliveira et al., 2022; Pazmiño et al., 2021; Pico et al., 2021; Prasad et al., 2020; Prasad et al., 2021; Real‐Ramírez et al., 2020; Robba et al., 2022; Robles et al., 2020; Rodriguez et al., 2021; Ruiz et al., 2021; Sagherian et al.,…”
Section: Resultsmentioning
confidence: 99%
“…Estes achados corroboram estudos que mostraram o adoecimento psíquico destes profissionais durante este período. [14][15][16][17][18][19][20] A compaixão em relação ao sofrimento e adoecimento de colegas foi um sentimento que mostrou acréscimo ao próprio desgaste dos trabalhadores. Durante a pandemia, fadiga por compaixão pelos colegas foi associada à exaustão emocional dos profissionais da enfermagem, 21 revelando mais efeitos negativos ao trabalhador que atuou neste período, principalmente pelo fato do apoio entre os colegas ser um recurso fundamental no enfrentamento de adversidades.…”
Section: Discussionunclassified